P200 A facility to enable high-quality, time-efficient evaluations of diagnostics for stis. (18th May 2015) - Harding-Esch, Emma; Pond, Marcus; Nori, Achyuta; Fuller, Sebastian; Chow, S-L Christine; Howell-Jones, Rebecca; Hall, Catherine; Harrison, Mark; Nardone, Anthony; Planche, Tim; Butcher, Philip; Lowndes, Catherine; et al.
Abstract : Background/introduction: Control of STIs is challenged by inadequate access to prompt diagnosis and treatment for patients and partners. Novel point-of-care diagnostics have real potential to address some of these challenges but their robust evaluation, and hence utility, is hampered by the ethics and regulatory landscape that confronts industry and academia. Aim(s)/objectives: To develop a diagnostics and clinical facility to deliver high-quality, time-efficient diagnostic evaluations for STIs. Methods: A multi-institutional and disciplinary group ( e STI 2 ) including clinical, public health and social scientists, microbiologists, clinicians, trial coordinators, and North American and European regulatory expertise was established. An 'overarching' ethics, favourable costing, and regulatory framework was carefully developed and put in place to enable any new diagnostic evaluation involving residual and/or additional-to-routine patient-consented samples to start promptly without requiring lengthy ethics applications. Strong working relationships with multiple GUM clinics were developed to overcome the potential for clinic fatigue, and Good Clinical Laboratory Practice Standard Operating Procedures were enabled. Results: Since February 2012, the network has conducted several evaluations with both academia and industry, spanning initial 'proof of concept' projects using residual samples, multi-site diagnostic evaluations involving >800 additional-to-routine patient samples completed in four months, and service evaluations of CE-marked assays. A diagnostic evaluation to support an application for regulatory approval will be taking place in 2015. Discussion/conclusion: The development of a diagnostic facility for STIs that fast-tracks high quality diagnostic evaluations is feasible and has potential for supporting promising diagnostic technologies towards NHS adoption.